Good Governance and Its Role in Achieving Sustainable Development Goals in Sudan: An Evaluative Study of Sudan’s Experience - Sulima, Sayda Mamoun; Elfaig, Hamid Hamad Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to research and analysis the role of good governance in achieving sustainable development goals in Sudan, focusing on the nature of governance and its commitment to implementing the 2030 Agenda. Information was collected from various sources, including books, references, journals, and online databases to achieve the study’s objectives. The study also relied on local and international reports, as well as other sources, and was supported by fieldwork that included interviews to gather both quantitative and qualitative data. The findings indicate that Sudan has achieved some aspects of good governance, particularly in promoting gender equality in civil service employment. However, the country remains far from achieving sustainable development goals, especially in the economic sector, where income inequality is widening, and poverty rates are increasing. Additionally, the environment suffers from desertification, land degradation, and biodiversity loss. The study recommends strengthening economic reforms to reduce poverty and improve the quality of life, in addition to adopting sustainable environmental policies to protect natural resources.